Q Fever: An Old but Still a Poorly Understood Disease - Honarmand, Hamidreza (Interdisciplinary Perspectives on Infectious Diseases, 2012)
Q fever is a bacterial infection affecting mainly the lungs, liver, and heart. It is found around the world and is caused by the bacteria Coxiella burnetii. The bacteria affects sheep, goats, cattle, dogs, cats, birds, rodents, and ticks. Infected animals shed this bacteria in birth products, feces, milk, and urine. Humans usually get Q fever by breathing in contaminated droplets released by infected animals and drinking raw milk. People at highest risk for this infection are farmers, laboratory workers, sheep and dairy workers, and veterinarians. Chronic Q fever develops in people who have been infected for more than 6 months. It usually takes about 20 days after exposure to the bacteria for symptoms to occur. Most cases are mild, yet some severe cases have been reported. Symptoms of acute Q fever may include: chest pain with breathing, cough, fever, headache, jaundice, muscle pains, and shortness of breath. Symptoms of chronic Q fever may include chills, fatigue, night sweats, prolonged fever, and shortness of breath. Q fever is diagnosed with a blood antibody test. The main treatment for the disease is with antibiotics. For acute Q fever, doxycycline is recommended. For chronic Q fever, a combination of doxycycline and hydroxychloroquine is often used long term. Complications are cirrhosis, hepatitis, encephalitis, endocarditis, pericarditis, myocarditis, interstitial pulmonary fibrosis, meningitis, and pneumonia. People at risk should always: carefully dispose of animal products that may be infected, disinfect any contaminated areas, and thoroughly wash their hands. Pasteurizing milk can also help prevent Q fever.